Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2466225
|View full text |Cite
|
Sign up to set email alerts
|

What makes you click

Abstract: Most studies take for granted the critical first steps that prelude interaction with a public display: awareness of the interactive affordances of the display, and enticement to interact. In this paper we investigate mechanisms for enticing interaction on public displays, and study the effectiveness of visual signals in overcoming the 'first click' problem. We combined 3 atomic visual elements (color/greyscale, animation/static, and icon/text) to form 8 visual signals that were deployed on 8 interactive public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The same space is also equipped with tables, chairs, and snack and drink machines, and is often used by students to study and socialize. As such, the location is a good representation of spaces commonly used in public display research [26,38,47,48,50,52,73,79,80]. In the real-world condition, participants were equipped with the Tobii Pro Glasses 2 wearable eye tracker to record their gaze data during the experiment.…”
Section: Apparatusmentioning
confidence: 99%
“…The same space is also equipped with tables, chairs, and snack and drink machines, and is often used by students to study and socialize. As such, the location is a good representation of spaces commonly used in public display research [26,38,47,48,50,52,73,79,80]. In the real-world condition, participants were equipped with the Tobii Pro Glasses 2 wearable eye tracker to record their gaze data during the experiment.…”
Section: Apparatusmentioning
confidence: 99%
“…An alternative approach is to add prompts that invite people to interact. For example, Kukka et al [32] compared the impact of static and dynamic icons and textual prompts (e.g., "touch me") in making people interact with the display, and found that text is more effective. The literature on the topic is, however, conflicting: other studies suggest that such "call-to-action" techniques are not that effective overall in communicating the interactivity of displays [42].…”
Section: Blindnessmentioning
confidence: 99%
“…Display blindness can apply equally to both interactive (i.e., PLIDs) and non-interactive (e.g., paper) displays, and has been observed extensively by HCI researchers in practice (e.g. [22,28]).…”
Section: Related Workmentioning
confidence: 99%
“…Interaction blindness occurs when a display is seen by someone, but is is not recognized as interactive [25,42]. Overcoming both display and interaction blindness is also referred to as the 'first click problem' [27,28,34].…”
Section: Related Workmentioning
confidence: 99%